2011
DOI: 10.1111/j.1740-0929.2011.00955.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of lactic acid bacteria isolated from mixed pasture of timothy and orchardgrass, and its badly preserved silage

Abstract: In order to understand the relationship between lactic acid bacteria (LAB) species and silage fermentation, a total of 65 LAB strains isolated from mixed pasture of timothy (Phleum pratense L.) and orchardgrass (Dactylis glomerata L.), and its badly preserved silages were subjected to phenotypic and genetic analysis. According to these analyses, the isolates were divided into 13 groups, including Enterococcus gallinarum, Lactobacillus acidipiscis, L. coryniformis subsp. coryniformis, L. coryniformis subsp. tor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…We also found here that three different isolates, each a member of a different lineage, were identified on the same meat slice, highlighting the challenge of identifying lineage niche specialization. L. sakei is most likely a bacterium that lives in agricultural areas [11], [35], [36], a habitat that contains several ecological niches (spatial and temporal) to which the species may have adapted, including pasture and barn environments, water fowl, silage, and the intestinal tracts of animals. Thus, the different evolutionary histories of L. sakei lineages might reflect adaptation to some of these microhabitats.…”
Section: Discussionmentioning
confidence: 99%
“…We also found here that three different isolates, each a member of a different lineage, were identified on the same meat slice, highlighting the challenge of identifying lineage niche specialization. L. sakei is most likely a bacterium that lives in agricultural areas [11], [35], [36], a habitat that contains several ecological niches (spatial and temporal) to which the species may have adapted, including pasture and barn environments, water fowl, silage, and the intestinal tracts of animals. Thus, the different evolutionary histories of L. sakei lineages might reflect adaptation to some of these microhabitats.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Tohno et al . () reported that the epiphytic lactic acid bacterial community on cocksfoot and timothy grasses is diverse and can potentially result in silages with a wide range of fermentation profiles.…”
Section: Discussionmentioning
confidence: 99%
“…The lactic acid bacteria (LAB) play important roles in adequate acidification and production of higher-quality silage. Some in vitro differences in available carbohydrates, optimal growth pH and temperature, are observed among different LAB strains, even within the same species and subspecies (Tohno et al, 2012a). To promote efficient fermentation in paddy rice silage, LAB should be added during the fermentation process.…”
Section: Introductionmentioning
confidence: 99%